Examining the value of money in england over the long term (1259-2009) - Abdullah, Adam (Canadian Center of Science and Education, 2013)
This paper seeks to analyze the value and purchasing power of money in England over 750 years, during which time the pound has lost almost all of its value. This paper proposes a suitable methodology of measuring nominal inflation in England over the long term, by constructing a wholesale commodity price index in order to determine the purchasing power of money, being the inverse of prices. The index adjusts indices of the value of gold and silver, to determine the purchasing power of gold, silver, and also real prices, thereby providing a suitable technique to measure the store of value function of money. In so doing, we discover that a monetary theory of value accurately interprets the empirical evidence.